Pemberdayaan Warga Desa Tawangargo dalam Penggunaan Food Dehydrator Pada Produk Pangan Olahan Dried Fruit and Vegetable (Druive) - Sanjaya, Yushinta Arsitina; Sarofa, Ulya; Suyuti, Ahmad; Widianti, Erika; Safa Asy’ari, Aidha (LPPM Universitas Trunojoyo Madura, 2023)
Fruits and vegetables are perishable commodities that require post-harvest handling such as drying processes to increase their life span. The inhabitants of Tawangargo Village work mostly as farmers, where the handling of fruits and vegetables commodities in fresh form or processed directly into various dishes. To increase the knowledge of the population, there is a need for training and exposure in the use of appropriate technology for food dehydrator as a tool for drying fruits and vegetables. The dedication program is carried out in the Tawangargo district of Karangploso district Malang with the aim of creating fruit and dry vegetables (druive) products through the design and training of the production of products with a process that is especially simple for members of the PKK. The results of the training are expected to enhance knowledge as well as to be an appropriate alternative technology product that can be used over a long period of time.